2014
DOI: 10.1245/s10434-014-4113-8
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Correlation of Residual Mammographic Microcalcifications After Neoadjuvant Chemotherapy for Locally Advanced Breast Cancer

Abstract: The extent of calcifications on mammography following NAC does not correlate with the extent of residual disease in up to 22 % of women; this information may impact surgical planning in subsets of women with breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 20 publications
1
36
0
5
Order By: Relevance
“…Only mammography can enable an accurate assessment of the extent of microcalcifications, which is essential to determine the extent of excision. Several studies have reported that decreases in the size and density of the tumor mass on a mammogram were the most reliable indicators of treatment response [137]. By contrast, the appearance of and changes in microcalcifications associated with malignancy have been deemed inaccurate for evaluating tumor response [137].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Only mammography can enable an accurate assessment of the extent of microcalcifications, which is essential to determine the extent of excision. Several studies have reported that decreases in the size and density of the tumor mass on a mammogram were the most reliable indicators of treatment response [137]. By contrast, the appearance of and changes in microcalcifications associated with malignancy have been deemed inaccurate for evaluating tumor response [137].…”
Section: Discussionmentioning
confidence: 99%
“…These microcalcifications decreased in four patients, were stable in 21, were more conspicuous in 15, and were newly developed in four. Adrada et al [1] found that the extent of calcification after neoadjuvant chemotherapy had decreased in 35 of 106 patients with advanced breast cancer, but it had remained stable in 41 patients and had increased or was newly developed in 30 patients. They did not find any correlation between calcification changes and pathologic complete remission.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations